Development of a Initialization and Supply Chain Resilience Model to Enhance Operational Performance in The Software Development Industry - Muhammad Mahdi; Jonny (Jurnal Penelitian Pendidikan IPA, 2025)
As an effort to enhance competitiveness and operational efficiency, it is essential for software development companies to continuously monitor and evaluate the operational performance of their supply chains. In the era of Industry 4.0, digitalization is imperative because the rapidly changing market dynamics can create vulnerabilities in the supply chain, making it necessary to strengthen the supply chain resilience of an industry. This research aims to develop a Model of Digitalization and Supply chain Resilience in the Software Development Industry and to test the variables that influence the operational performance of the supply chain. Data in this study is collected through questionnaires addressed to operational managers specifically in the field of supply chain. The data will be tested using Structural Equation Modeling with the help of SMART-PLS software. It is hoped that the results of this research can serve as a reference and recommendation for academics and practitioners regarding the model of digitalization and supply chain resilience in the software development industry.